If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1(-4 + -6y) + 7(-1y + 5) = -8 3 + (-4 * -1 + -6y * -1) + 7(-1y + 5) = -8 3 + (4 + 6y) + 7(-1y + 5) = -8 Reorder the terms: 3 + 4 + 6y + 7(5 + -1y) = -8 3 + 4 + 6y + (5 * 7 + -1y * 7) = -8 3 + 4 + 6y + (35 + -7y) = -8 Reorder the terms: 3 + 4 + 35 + 6y + -7y = -8 Combine like terms: 3 + 4 = 7 7 + 35 + 6y + -7y = -8 Combine like terms: 7 + 35 = 42 42 + 6y + -7y = -8 Combine like terms: 6y + -7y = -1y 42 + -1y = -8 Solving 42 + -1y = -8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -1y = -8 + -42 Combine like terms: 42 + -42 = 0 0 + -1y = -8 + -42 -1y = -8 + -42 Combine like terms: -8 + -42 = -50 -1y = -50 Divide each side by '-1'. y = 50 Simplifying y = 50
| 2x+90=5c | | -15-7e=-22 | | 10m+20m^2=0 | | 15i=-75 | | .9x=15.3 | | -5.5+.56=-1.46 | | -2k+4k-5+5k= | | -17160+1859m=909m-1010 | | -.5(24+6x)=-3(x-4) | | 7/9*3/8 | | 25=51/w | | -x+27=2x+6 | | x^2+35x=105 | | 4x-21=7(x+9) | | 2x+8-22x=-10 | | F(x)-7whenF(x)=3X-2 | | 112=(-16t^2)+64t+48 | | 21/4.2 | | 8x-1/2x | | 2/3*5/8 | | 4x-1=4x-2 | | 1/7•10 | | 2.7x+4=(10+x).7 | | -4k^2+4K-1=0 | | .12x+.8y=40.4 | | -3x+-12+15=6-4x | | 2z+7y=z | | -2.4=6.8(x-0.3) | | 7/8*2/9 | | 1/4k=3(-1/4k=3) | | 100x^2-625=0 | | 8m-4=8-5m-10m |